The effect of the mentimeter-based brainstorming method on secondary school students' critical thinking skills - Nabila, Cut Akhwalul; Maimun; Irwan Putra (International Journal of Advances in Educational Research, 2025)
This study examines the effect of the Mentimeter-based brainstorming method on students' critical thinking skills in the teaching of Pancasila and Civic Education (PPKn). The purpose of this research is to determine the impact of implementing the Mentimeter-based brainstorming method on students’ critical thinking abilities. The background of this study is based on the importance of developing critical thinking skills as a demand of 21st-century learning, in which students are expected to be able to analyze, evaluate, and express their opinions logically and reflectively. This research employs a quantitative approach using a quasi-experimental design with a nonequivalent control group type. The sample consists of two classes divided into an experimental group and a control group. The instrument used was a set of multiple-choice questions designed to measure indicators of critical thinking. Data analysis was conducted using SPSS version 24. The results of the study show a significant difference between the post-test scores of the experimental and control groups. Students who participated in learning using the Mentimeter-based brainstorming method showed greater improvement in critical thinking skills compared to those who learned through conventional methods. These findings confirm that the integration of interactive technology into active learning models can create a participatory, reflective, and democratic learning environment. This study recommends the use of Mentimeter as a strategic innovation to enhance students' critical thinking skills across various educational levels.